Effects and synergy of feed ingredients on canine neoplastic cell proliferation. Issue 1 (December 2016) - Levine, Corri; Bayle, Julie; Biourge, Vincent; Wakshlag, Joseph
Abstract Background Adjunctive use of nutraceuticals in human cancer has shown promise, but little work has been done in canine neoplasia. Previous human research has shown that polyphenols and carotenoids can target multiple pathways in vitro and in vivo. These compounds could synergize or antagonize with currently used chemotherapies, either increasing or decreasing the effectiveness of these drugs. Considering the routine and well controlled feeding practices of most dogs, the use of nutraceuticals incorporated into pet food is attractive, pending proof that the extracts are able to improve remission rates. The aim of this study was to examine five feed ingredients for antiproliferative effects, as well as the interaction with toceranib phosphate and doxorubicin hydrochloride, when treating canine neoplastic cell lines in vitro. Results Screening using MTT proliferation assays showed that green tea, turmeric, and rosemary extracts were the most effective. Turmeric extract (TE) was the most potent and exhibited synergy with a rosemary extract (RE) at concentrations from 1 to 25 μg mL−1 . This combination had an additive or synergistic effect with chemotherapeutic agents at selected concentrations within each cell line. No significant effects on cell viability were observed when the combination therapy was used with normal primary cells. Conclusions The use of turmeric and rosemary extracts in combination may be worthwhile to investigate in the pre-clinical and clinical neoplastic considering there are no negative effects on traditional chemotherapy treatment. Further studies into the pharmacokinetics and mechanisms of action of these extracts should be investigated.